Screening and identification of bacteriocin-producing lactic acid bacteria from Thai fermented meat products - Krongkeha, Watcharacha (RMUTSB ACADEMIC JOURNAL, 2024)
Bacteriocins are peptides that inhibit food pathogens and are produced by both gram-positive and gram-negative bacteria. The objective of this study was to screen, isolate, and identify bacteriocin-producing lactic acid bacteria (LAB) from Thai fermented meat products. A total of 91 isolates were obtained and screened for bacteriocin production. Eight isolates exhibited remarkably wide zones of inhibition based on the agar well diffusion technique against foodborne pathogens, including Listeria monocytogenes, Escherichia coli and Staphylococcus aureus. These isolates are gram-positive bacteria and rod-shaped, except for NF-11, which is round-shaped. The biocatalytic activity of these eight isolates was sensitive to proteolytic enzymes. The results of nucleotide sequences of the 16S rRNA genes revealed that PS-5, PS-7, PS-8 and PJ-5 isolated from Pla-som and Pla-jom were identified as Lactiplantibacillus pentosus. MU-9, SK-1 and SK-6 isolated from Mum-moo and Sai-krok were identified as Lactiplantibacillus plantarum, while NF-11 isolated from Nham-pla was identified as Pediococcus pentosaceus. These selected LAB have the potential to be developed as starter cultures in the fermented food industry.